Protective Effects of Apis Dorsata Honey Supplementation on Kidney Histopathology in Mice with Monosodium Glutamate Exposure - Rao, Sherbrina Bai Seenivasa; Widjiati, Widjiati; Lokapirnasari, Widya Paramita; Triakoso, Nusdianto; Safitri, Erma; Kuncorojakti, Suryo; Proboningrat, Annise (Jurnal Medik Veteriner, 2023)
This study was conducted to investigate the protective effects of Apis dorsata honey on the histopathological changes of the kidney in mice exposed to monosodium glutamate. This study used 25 male mice as the experimental animal which were divided into five groups with five replication, respectively i.e. (C-) was administered basal diet, (C+) was administered 4 mg/g BW MSG, (T1) was administered A. dorsata honey of 53.82 mg/20g BW followed by MSG 4 mg/g BW, (T2) was administered A. dorsata honey of 107.64 mg/20g BW followed by MSG 4 mg/g BW, and (T3) was administered A. dorsata honey of 161.46 g/20g BW followed by MSG 4 mg/g BW. All treatments were carried out orally for 52 days. This study was observed tubular epithelial hydropic degeneration, epithelial necrosis, and glomerular necrosis. Data were analyzed using Kruskal-Wallis test followed by the Mann-Whitney test. As a result, for the epithelial and glomerular necrosis variables, the T3 group showed significant results when compared with C+, T1, and T2 groups. Moreover, T3 was not significantly different from the C- group. It can be concluded that A. dorsata honey in T3 group could protect mice kidneys from the damaging effect of MSG.